Diagnostic procedure for idiopathic eosinophilic pleural effusion: a single-center experience - Luo, Weizhan (BMC Pulm Med, 2020)
BACKGROUND: Eosinophilic pleural effusion (EPE) is attributed to several well-recognised causes. However, some patients remain idiopathic, even after thorough clinical work-up. The present study aimed to better characterize idiopathic EPE (IEPE) and to outline the diagnostic procedure for this disease. METHODS: Complete clinical data of 11 consecutive patients with IEPE were prospectively collected and analysed. Preliminary diagnostic procedure of IEPE in our hospital was performed. RESULTS: All the 11 patients had respiratory symptoms and unilateral pleural effusion (PE) occurred in 4 patients. The mean percentage of eosinophils in PE was 22.4% (range, 12.4–50.5%). Lactate dehydrogenase, adenosine deaminase, proteins and carcinoembryonic antigen in PE were 246.0 U/L (range, 89.8–421.9 U/L), 13.8 U/L (range, 1.8–24.0 U/L), 42.6 g/dl (range, 32.8–52.6 g/dl) and 2.17 mg/mL (range, 0.46–4.31 mg/mL), respectively. Parasite-specific IgG antibody in blood and parasite eggs in stool were both negative. No evidence of tuberculosis or malignancy was observed in pleural biopsy. Symptoms and abnormal pulmonary imaging were eliminated after glucocorticoid use. CONCLUSIONS: IEPE is a diagnosis of exclusion. Patients with EPE without a clear cause should be asked to provided complete medical, surgical and drug-related histories. A thorough work-up is essential. Moreover, we recommend follow-up after the use of glucocorticoid until effusion resolves. TRIAL REGISTRATION: GYFYY. Registration No: GYFYY20150901221. Registered time: 1 September 2015. Date of enrolment of the first participant to the trial: 22 January 2016.